INTENSITAS SERANGAN PENYAKIT TANAMAN JABON (Anthocephaluscadamba) PADA HUTAN TANAMAN DI JALAN RAYA PASIR PUTIH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Ariska Yuliana Putri; M. Mardhiansyah; Evi Sribudiani (JURNAL ILMU-ILMU KEHUTANAN, 2019)
Anthocephalus cadamba can be used as one of the alternative plantations because Anthocephalus cadamba is a fast-growing plant species. Disorders by disease attacks can reduce the quality and quantity of wood in the Anthocephalus cadamba stands. Diseases that attack a plant forest population can be very destructive and accompanied by symptoms and signs. Disease attacks will result imbalanced ecosystem if it is not properly considered. The purpose of this research was to determine the intensity of disease attacks on Anthocephalus cadamba stands. Research conducted on Anthocephalus cadamba stands that have an area of 2 ha with a plant distance of 3m x 4m using the survey method showed the intensity of disease attacks on Anthocephalus cadamba stands at Raya PasirPutih street was 24,75%. The most common criteria for the attack of Anthocephalus cadamba disease are mild attacks by 91,0%, then healthy by 5,5%, then moderate attacks by 2,5% and the least were severe attacks by 1,0% of 800 Anthocephalus cadamba stands.The disease that attacks the Anthocephalus cadamba stands were leaf spot, flour dew, soot dew and stem cancer.